Contribuição para o conhecimento de Collembola entomobryomorpha (Insecta) do Parque Nacional da Tijuca, Rio de Janeiro, Brasil - Mendonça, Maria Cleide de (1981)
Taxonomic and distributional study of the springtails belonging to the suborder Entomobryomorpha from Parque Nacional da Tijuca is presented. Sixty samples with 31.403 specimens were collected at eleven different localities from February 1979 through February 1980. Twenty species, incluing one not previously described were selected based on their occurrence and frequency. Based on the morphology of the species we constructed an identification key for the Entomobryomorpha of the local fauna, The terminology usually used for springtails, is also given. For each species besides careful characterization, including overlooked characters a survey of its know geographical distribution, and comments on its taxonomy and ecology is also given.